Policy Style and The US Policy Response to the COVID-19 Pandemic: A Rebuttal to Lawrence D. Brown’s Fomenters of Fiasco - Kristin Taylor; Rob DeLeo; Thomas Birkland; Deserai Anderson Crow (International Review of Public Policy)
Through the lens of policy style that we respectfully disagree with Professor Brown’s assessment of the United States’ botched COVID-19 pandemic response as being exclusively or even primarily explained by electoral concerns. Although we agree that the electoral concerns of many actors in the response were important, reducing every aspect of the botched policy response to the COVID-19 pandemic to an electoral calculus is far too narrow. It overlooks important factors, particularly the interaction between public trust in government and a country’s policy style during times of crisis.